Teachers’ attitude towards their profession - Kregždienė , O. (Psichologija, 1969)
429 town and country teachers of the Lithuanian SSR were interrogated. The investigation of a semi-secret questionnaire and personal talks revealed that 50 percent of the total number entertained a negative attitude towards their profession, irrespective of the length of service. They would change their profession were it possible, they said. The motives of their professional choice play a most important part in their later attitude towards the chosen profession. 85 percent of those, whose attitude towards their profession is positive, were guided in their choice by love for children, social significance of the profession, pedagogical skills. The main motives of choice of those who dislike their profession were: situation, family status, possibility to study, love of a definite subject, etc. In the end a conclusion is drawn that in preparing good, loving their profession, teachers’ selection of candidates to pedagogical institutes should be considered; that professional tenor, finding its expression in the motives of choice, plays a decisive part.